Positive interactions between the lichen Usnea antarctica (Parmeliaceae) and the native flora in Maritime Antarctica. (25th September 2012) - Molina‐Montenegro, Marco A.; Ricote‐Martínez, Natalia; Muñoz‐Ramírez, Carlos; Gómez‐González, Susana; Torres‐Díaz, Cristian; Salgado‐Luarte, Cristian; Gianoli, Ernesto; Woods, Kerry
Abstract Questions Is the macrolichen Usnea antarctica a 'nurse' species to Antarctic flora? Are positive plant–plant interactions more frequent than negative interactions in Antarctic ecosystems? Are microclimatic modifications by cushions of U. antarctica responsible for the nurse effect? Location Two sites in Antarctica: King George Island, South Shetland (62°11′ S, 58°56′ W; 62°11′ S, 58°59′ W). Methods We evaluated the association of plant species with U. antarctica cushions by recording species growing – in equivalent areas – within and outside U. antarctica cushions. Additionally, we performed transplant experiments with Deschampsia antarctica individuals to assess if U. antarctica cushions enhance plant survival. In both study sites we monitored temperature, moisture and nutrient status of soil outside and within the cushions to provide insights into potential mechanisms underlying possible interactions between U. antarctica and other plant species. Results Eight out of 13 species were positively associated with cushions of the widespread lichen U. antarctica, while only one species (U. aurantiaco‐atra) showed a negative association with U. antarctica. Survival of Deschampsia was enhanced when growing associated with U. antarctica cushions. Our results indicate that cushions ameliorated the extreme conditions of Antarctic islands through increased temperature and soil moisture, decreased radiation and evaporative water loss and increased nutrient availability. Conclusions The nurse effect of U. antarctica is verified. Cushions of this macrolichen may be a key component in structuring the Antarctic landscape and maintaining local species richness, and their presence might influence range expansion of other species.